Pengaruh Lingkungan Keluarga Terhadap Minat Wirausaha Melalui Self Efficacy - Dhika Bayu Mahardhika; Baihaqi Akbar; Cahyandi Falah; Daniel Pernando Simarmata; David Wijanarko Purma; Dimas Pratama (Peneliti.net, 2023)
The purpose of this study was to find out how the influence of entrepreneurial knowledge and family environment on the interest in entrepreneurship as an intermediate variable of self-efficacy. The basic population of this study consisted of 114 students after processing the Slovin formula with a standard error of 5%. In this study, a questionnaire was used as a data collection tool. Descriptive analysis, path analysis and Sobel's test were used to analyze the data. The results showed that 1) knowledge of entrepreneurship had a positive and significant effect on the interest in entrepreneurship, 2) the family environment had no positive and significant effect on the interest in entrepreneurship, 3) self-efficacy had a positive and significant effect. about entrepreneurship Interest in entrepreneurship 4) Knowledge of entrepreneurship has a positive and significant effect on self-efficacy 5) Family environment has a positive and significant effect on self-efficacy 6) Knowledge of entrepreneurship has a positive and significant effect on entrepreneurship interest through self-efficacy 7) Family environment has a positive and significant effect significantly to the interest in entrepreneurship through self-efficacy. The conclusions from this study indicate that entrepreneurial competence and family environment have a positive and significant effect on the interest in entrepreneurship through self-efficacy.